2008
DOI: 10.1111/j.1467-8519.2008.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability in Research and Health Care; Describing the Elephant in the Room?

Abstract: Despite broad agreement that the vulnerable have a claim to special protection, defining vulnerable persons or populations has proved more difficult than we would like. This is a theoretical as well as a practical problem, as it hinders both convincing justifications for this claim and the practical application of required protections. In this paper, I review consent-based, harm-based, and comprehensive definitions of vulnerability in healthcare and research with human subjects. Although current definitions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
219
0
21

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(241 citation statements)
references
References 32 publications
1
219
0
21
Order By: Relevance
“…The reasons are to be found in the methodical challenges, since due to the expected low prevalence a large sample is required in order to be able to identify the target group at all. It is also extremely difficult to gain access to the target group [5,23,27,35]. During the whole research period only one survey from Austria was identified [5], the results of which could be roughly compared with the previous parameters from Great Britain [4,36].…”
Section: Discussionmentioning
confidence: 91%
“…The reasons are to be found in the methodical challenges, since due to the expected low prevalence a large sample is required in order to be able to identify the target group at all. It is also extremely difficult to gain access to the target group [5,23,27,35]. During the whole research period only one survey from Austria was identified [5], the results of which could be roughly compared with the previous parameters from Great Britain [4,36].…”
Section: Discussionmentioning
confidence: 91%
“…The comparative advantages of this definition are recognized in the focused attention on the characteristics of the environment rather than on the characteristics of the subjects; in broadening the scope of vulnerability as it remains open to the multiple nature of potential wrongs and sources of greater likelihood of suffering them; it conceptually dislocates the claim to special protection of the vulnerable outside of vulnerability itself to some other valid source; and practical usefulness in both research ethics and clinical ethics. As one of the limitations of the proposed definition, Hurst states that it excludes forms of vulnerability associated in general to being human, that is, the definition stays within the spectrum of special vulnerability (Hurst, 2008). The controversy concerning the two disparate views on the scope of vulnerability is addressed in a later article.…”
Section: The Concept Of Invulnerabilitymentioning
confidence: 99%
“…ATTEMPTS AT RESOLUTION Samia A. Hurst (2008) assumes that a definition of vulnerability should consist of a claim to special protection. A definition that includes humanity, such, for example, as the one provided in the Barcelona Declaration, is thus considered as too broad as it does not provide reasons for special protection.…”
Section: The Concept Of Invulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…One way to synthesize these different definitions, and to make headway towards defining what protections are needed, is to consider that vulnerability as a claim to special protection is any identifiably increased likelihood of being wronged (Hurst 2008).…”
Section: Can Persons With Cognitive Impairment Be Enrolled In Research?mentioning
confidence: 99%